The end of the free market who wins the war between states and corporations? - Bremmer, Ian 1969- (Portfolio, 2010)
This work details the growing phenomenon of state capitalism, a system in which governments drive local economies through ownership of market-dominant companies. This trend, Bremmer argues, threatens America's competitive edge and the conduct of free markets everywhere.